Tracking terrorism and counter-terrorism: Introducing the Turkey terrorism incidents database - Alptekin, Hüseyin (Routledge, 2023)
This research note presents an original dataset on PKK terrorism incidents in Turkey based on an extensive review of the Turkish-language newspapers. The dataset contains 4579 events, coded across 68 variables, and over the course of 15 years from 2004 to 2018. The article discusses the scope and included variables of the dataset and provides insight into how the PKK engaged in terror attacks and how the Turkish security forces (military, police, and village guards) carried out counterterrorism operations.
Keywords: Terrorism; Counterterrorism; Insurgency; Turkey; PKK